Renta ekonomiczna - "nowa" perspektywa zarządzania strategicznego - Stańczyk-Hugiet, Ewa (Economic Rents - "New" Perspective in Strategic Management, 2008)
The paper presents different kinds of economic rents. Economic rent's sources are the sources of competitive advantage. Economic rent has important implications across strategic management - it is a path in making strategic decisions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 223-233